Advances in MALDI Mass Spectrometry Imaging Single Cell and Tissues - Zhu, Xiaoping; Xu, Tianyi; Peng, Chen; Wu, Shihua (Frontiers in Chemistry, 2022)
Compared to conventional optical microscopy techniques, mass spectrometry imaging (MSI) or imaging mass spectrometry (IMS) is a powerful, label-free analytical technique which can sensitively and simultaneously detect, quantify and map hundreds of biomolecules such as peptides, proteins, lipid and other organic compounds in cells and tissues. So far, although several soft ionization techniques such as desorption electrospray ionization (DESI) and secondary ion mass spectrometry (SIMS) have been used for imaging biomolecules, matrix-assisted laser desorption/ionization (MALDI) is still the most widespread MSI scanning methods. Here, we aim to provide a comprehensive review of MALDI-MSI with an emphasis on its advances of the instrumentation, methods, application and future directions in single cell and biological tissues.